Decentralized Academic Platforms: The Future of Education in the Age of Blockchain - Berlin Any; Ramadhan, Tarisya; Alwiyah; Efa Ayu Nabila (IAIC Bangun Bangsa, 2024)
Despite referring to two different phenomena, the phrases